Understanding heatwave-drought compound hazards and impacts on socio-ecosystems - Yin, J; Slater, L (Innovation Press, 2023)
As the Earth warms, the frequency and severity of weather and climate-related extremes are steadily increasing in most regions worldwide. A critical concern is the simultaneous occurrence of climatic extremes in the same location, referred to as compound events. Among these, Heatwave-Drought Compound Events (HDCEs) are one of the most destructive hazards, exacerbating impacts on human societies and ecosystems more than individual extremes. Therefore, it is necessary to understand the physical mechanisms behind HDCEs and to project their future changes and implications for socio-ecosystems. In this Perspective, we explain the motivation for understanding HDCE dynamics, describe new protocols to explore the water-heat-carbon coupling processes driving HDCEs, and finally outline future changes in HDCEs as well as their impacts on economic development and the carbon cycle.